Traitorousness to homeland: A mechanism of revelation and exclusion in the Late Ottoman Empire and Early Republican Turkey - Arslan, Onur (İstanbul Bilgi Üniversitesi, 2015)
Bu çalışmanın amacı geç Osmanlı İmparatorluğu ve erken Türkiye cumhuriyeti bağlamında vatan-hainliği kavramı ve kendiliğin oluşturulması arasında bir ilişki kurmaktır. Veriler Yunan, Sırp, Türk ve Ermeni devrimcilere/milliyetçilere ait beyanlardan elde edildi. Ayrıca vatan hainlerinin dışlanmasını ve ifşaatını incelemek için ilgili tarihsel olaylar seçildi. Elde edilen sonuçların ışığında, vatan hainliğini devletin hukuksal söylemiyle sınırlamaktan ziyade kendiliğin dönüşümünde bir dispozitif olarak işlediğini savundum. Bu sebeple, ilk olarak, geç Osmanlı İmparatorluğu'nda vatan, vatan hainliği, vatana ihanet, vatandaşlık ve vatanseverlik kavramları arasındaki kompleks ilişkiye odaklandım. Bu kavramların nasıl mahşeri (kıyametsel) bir mahiyet kazandığına cevap aradım. İkincil olarak, vatan hainliğinin hükümranla yapılan toplumsal sözleşmenin ihlalinin bir yaptırımı olarak mı, yoksa belirli bir kollektif kimlik tarafından dayatılan norm ve değerlere kayıtsızlığın bir sonucu olarak mı ortaya çıktığını araştırdım. Son olarak, hainin benliğine yönelik metafiziksel sorgulamayı tartışarak, vatan hainlerinin ifşaatının-dışlanmasının ifşa edenin özbenliğini nasıl şekillendirdiğini göstermeye çalıştım. Anahtar Kelimeler: Vatan, vatan hainliği, vatana ihanet, kendilik, Osmanlı İmparatorluğu

The aim of this study is to establish a correlation between the concept of traitorousness-to-homeland and the constitution of the essential self within the context of the late Ottoman Empire and the early republican Turkey. Data for this study were obtained from the statements of Greek, Serbian, Turkish and Armenian revolutionaries/nationalists. Also, relevant historical events were selected to examine the exclusion and revelation of traitors to homeland. In the light of obtained results, I argued that traitorousness to homeland functioned-as-apparatus (dispositif) which transformed the essential self, rather than confining this apparatus to the juridical discourse of state power. For this reason, at first, I focused on the complex relationship between homeland, traitorousness to homeland, high treason, citizenship and patriotism in the late Ottoman Empire, and I tried to find out how these concepts gained an apocalyptic nature in the political relations. Secondarily I investigate whether traitorousness to homeland sprung up as the sanction of violating a social contract with the sovereign, or the result of being indifference to the norms and values which were imposed by a particular collective identity. Lastly, I tried to demonstrate how the revelation-exclusion of traitors to homeland shaped the exposers' essential self by discussing the metaphysical investigation over the self of the traitor. Keywords: Homeland, Traitorousness to homeland, high treason self, Ottoman Empire
Vatan hainliği: Geç Osmanlı İmparatorluğu ve Erken Türkiye Cumhuriyeti'nde bir ifşaat ve dışlama mekanizması